A study on the adequacy of the laws governing the sale of medicines by online pharmacies in Malaysia / Muhamad Helmi Ismail and Mohd Zairul Khusairy Mohd Zawawi - Ismail, Muhamad Helmi; Mohd Zawawi, Mohd Zairul Khusairy (Faculty of Law, 2015)
The risk and danger associated with illegal online sale such as online prescriptions without prior physical examination by a doctor, purity and quality of drugs, medical and financial privacy concerns, and abuse of medicines has been elaborated in this research. This research focus on the adequacy of the current laws in governing the online sale of medicines. This study is to focus on two (2) main statutes namely the Poison Act 1952 and the Sale of Drug Act 1952. In addition, other cyber laws such as the Computer Crimes Act 1997 and the Communications and Multimedia Act 1998 have also been analyzed in this research. A comparison with other jurisdiction such as the UK and the USA has also been discussed in this research. This study adapted a combination of doctrinal and empirical research approach. The semi structured interviews had been conducted during the period of research with the respondents from the Pharmaceutical Enforcement Department (PED). This research found that the current laws governing the online sale of medicines are not adequate. The inadequacies can be found in the aspects of dealing evident in internet medium and limitation of power in investigation. There are several recommendations that had been suggested in this research. One of them is to come out with a clear guideline related to the online sale of medicines. Another recommendation is to amend the Poison Act 1952 and the Sale of Drug Act 1952 in order to adequately govern the online sale of medicines.